The Effect of Human Development Cadre Mentoring on Knowledge and Attitude of Stunting Prevention in Pregnant Women in Sragen - Eny, Eny; Dwiyanti, Danik (Universitas Mandala Waluya, 2025)
Stunting is a condition that is said to be malnourished, thus affecting infants both before birth and early after birth which is analysed from several factors including maternal size, nutrition during pregnancy, and fetal growth. The lack of information obtained by pregnant women affects knowledge and attitudes, especially about preventing stunting during pregnancy. This study aims to determine the effect of development cadre assistance (KPM) on knowledge and attitudes in preventing stunting in first and second trimester pregnant women in Sragen. This study used a Quantitative approach, this type of research is experimental, quasi-experimental design with a sub-design of one group pre-test and post-test only one group, without a control group. The sample was determined using purposive sampling, the intervention was given to 38 pregnant women in trimester 1 and 2, data analysis using the Friedman test. The results showed that there was an effect of KPM assistance on knowledge and attitudes in preventing stunting. So with these significant results, it is hoped that the sragen district government can empower KPM so that data collection on the 1000 HPK target, besides that KPM can become a companion, especially in providing education related to stunting prevention.